2013
DOI: 10.1007/s12253-013-9728-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1α and its Role in the Proliferation of Retinoblastoma Cells

Abstract: In order to better understand the role of HIF-1α in the proliferation of the retinoblastoma cells, a siRNA knockdown of HIF-1α followed by a proliferation assay was performed. Further sequencing was then carried out in order to assess knockdown efficiency and expression of HIF-1α. Upregulation of HIF-1α gene expression in CoCl2-treated retinoblastoma cells was demonstrated via melting curve analysis from PCR tests and was further analyzed using western blot and densitometry analysis. Reduction of HIF-1α expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This is reasonable since HIF-1α is also detectable under normoxia in tumor tissues. 20,[36][37][38] In the following studies, the role of MIR17HG/miR-155-5p/HIF-1α in RB in hypoxic microenvironment should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This is reasonable since HIF-1α is also detectable under normoxia in tumor tissues. 20,[36][37][38] In the following studies, the role of MIR17HG/miR-155-5p/HIF-1α in RB in hypoxic microenvironment should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α is an oxygen-dependent subunit of HIF-1, which has another constitutively expressed (HIF-1β subunit); HIF-1α and HIF-1β are members of the basic helix-loop-helix-Per-ARNT-Sim (bHLH-PAS) protein family (17). In previous studies, deregulated HIF-1α was observed in RB hypoxic regions (18), and HIF-1α levels were associated with the survival and proliferation of RB cells (19). Therefore, we hypothesized that miR-320 may affect RB development by influencing HIF-1α levels.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, Rb tumors undergo ongoing hypoxic adaptation to allow continued proliferation and invasion in an increasingly oxygen-depleted environment ( 47, 48 ), and our findings implicate ESRRG and its decoupling from normal homeostatic regulation by RB1 and BCOR as a key mediator of this hypoxic adaptation. Further studies are warranted to investigate the potential role for inhibiting ESRRG in the management of Rb.…”
Section: Discussionmentioning
confidence: 62%